2015
DOI: 10.4306/pi.2015.12.3.335
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Taekwondo Training on Brain Connectivity and Body Intelligence

Abstract: ObjectiveMany studies have reported that Taekwondo training could improve body perception, control and brain activity, as assessed with an electroencephalogram. This study aimed to assess body intelligence and brain connectivity in children with Taekwondo training as compared to children without Taekwondo training.MethodsFifteen children with Taekwondo training (TKD) and 13 age- and sex-matched children who had no previous experience of Taekwondo training (controls) were recruited. Body intelligence, clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 31 publications
1
15
0
1
Order By: Relevance
“…More specifically, Brown et al reported that a 9-week aerobic exercise program resulted in a significant increase in the Vigor-Activity score 13 ) , whereas Sakuragi and Sugiyama reported that a 4-week walking exercise program led to a significant reduction in the Tension-Anxiety and Anger-Hostility scores 14 ) . In particular, TKD training during childhood has been reported to promote emotional and social development, mitigate anxiety, improve independence and leadership, and effectively control aggression 15 , 16 ) , all of which support the findings of our study. Additionally, TKD exercise was effective for improving Vigor, Anxiety, Depression, Anger, Fatigue, and Confusion among POMS sub-variables 17 ) .…”
Section: Discussionsupporting
confidence: 89%
“…More specifically, Brown et al reported that a 9-week aerobic exercise program resulted in a significant increase in the Vigor-Activity score 13 ) , whereas Sakuragi and Sugiyama reported that a 4-week walking exercise program led to a significant reduction in the Tension-Anxiety and Anger-Hostility scores 14 ) . In particular, TKD training during childhood has been reported to promote emotional and social development, mitigate anxiety, improve independence and leadership, and effectively control aggression 15 , 16 ) , all of which support the findings of our study. Additionally, TKD exercise was effective for improving Vigor, Anxiety, Depression, Anger, Fatigue, and Confusion among POMS sub-variables 17 ) .…”
Section: Discussionsupporting
confidence: 89%
“…It has also been reported that the number of children participating in TKD is increasing globally [ 11 , 12 , 13 ]. Several recent studies have reported the significant health benefits of regular TKD training [ 11 , 13 , 14 , 15 ]. For example, Fong and Ng (2011) critically reviewed 23 TKD-related papers and investigated the effect of regular TKD training on the improvements in physical fitness [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Lee and Kim reported that TKD training can be effective in improving physical fitness and growth and development in children [ 13 ]. By using functional magnetic resonance imaging to observe the brains of children who participated in regular TKD training, Kim et al reported a significant improvement in the activation of the brain, implying that TKD training can have a positive effect on the growth and development, fitness, and certain aspects of the health of the brain including cognitive function [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence suggests that environmental factors (e.g., diet) and lifetime experiences (e.g., cognitive training, exercise, and substance abuse) may alter brain connectivity [58][59][60][61]. In one study, adaptive working memory training altered connectivity between frontoparietal networks and both the lateral occipital complex and inferior temporal cortex.…”
Section: Environmental Factors and Lifetime Experiencesmentioning
confidence: 99%